(untitled) (Research, Society and Development, 2021)
This study aims to assess the role of nurses in preventing puerperal infection associated with Cesarean surgery. Methodology: This is an integrative review, analytical and retrospective, with a qualitative approach. The first step is composed by the delimitation of the theme, which was defined as: Nursing Care in the prevention of Puerperal Infection in Cesarean Delivery, to answer the guiding question: What Nursing Care in the intra-hospital environment can prevent puerperal infection in childbirth Caesarean? Results: Through the analysis of the full texts, 07 articles were fully evaluated, which met the inclusion criteria set out in the methodology of this research. Final Considerations: It is concluded that there are associated risk factors that are determinant for Puerperal Infection in Cesarean Delivery and that the Nursing professional must adopt scientifically-based care for their applicability, as the nurse is responsible for managing the risks, notify adverse events, and mainly act in order to prevent and reduce infections in the hospital environment.